The effect of central corneal thickness on intraocular pressure values using various tonometers in the dog. (22nd February 2021) - Guresh, Andrew M.; Horvath, Stephen J.; Gemensky‐Metzler, Anne; Miller, Eric; Yildiz, Vedat; Myers, John V.; Newbold, Georgina M.
Abstract: Objective: To compare intraocular pressure readings from three different tonometers, the Tono‐Pen AVIA® (TP), TonoVet® (TV) and TonoVet Plus® (TV+) and to determine how measurements from each tonometer are affected by central corneal thickness (CCT). Animals: Ninety dogs. Procedures: Normal dogs and dogs with ocular disease were selected for study inclusion. Central corneal thickness measurements were gathered with the Pachette 4 ultrasonic pachymeter, and IOP measurements were gathered with the three tonometers in random order. ANOVA or Wilcoxon tests were utilized for overall group comparisons. Linear regression analyses were utilized to determine the association between IOP and CCT. Results: When comparing tonometers to each other, for all dogs, readings from the TV+were significantly different compared to the TV ( p  = <.0001) and TP ( p  = <.0001); however, there was no significant difference between the TV and the TP ( p  = .999). Linear regression did not find any significant correlation between corneal thickness and IOP readings with any tonometer when looking at normal dogs or when including dogs with ocular abnormalities. Discussion: This study did not find a significant correlation between an increase in CCT and increase in IOP reading in any tonometer comparison amongst normal and dogs with ocular abnormalities. The TV+produced consistently and significantly higher readings, but measurements did not exceed the expected IOP range in normal dogs. For consistency, the same tonometer should be used when monitoring IOP over time.